The diversity, ethnobotany and nutrient contents of Dioscorea for post-disaster food security in Lombok, Indonesia - INDRIYATNO INDRIYATNO; NURHENI WIJAYANTO; IRMANIDA BATUBARA; SUPRIYANTO SUPRIYANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Indriyatno, Wijayanto N, Batubara I, Supriyanto. 2024. The diversity, ethnobotany and nutrient contents of Dioscorea for post-disaster food security in Lombok, Indonesia. Biodiversitas 25: 553-564. Earthquakes caused damage to infrastructure, houses, and roads in Lombok in 2018. After the earthquake, there was a shortage of food. Adaptation to address food shortage can be overcome by using local food sources, including those from the Dioscorea genus. The study aims to analyze the diversity and distribution, ethnobotany and nutrient contents of the Dioscorea genus in Lombok Island. Botanical explorations were conducted to identify the intraspecific varieties in the form of local types/names complemented with ethnobotanical study through structured interviews. The nutrient contents were determined using a standardized method in proximate analysis. The study found 12 local types of Dioscorea belonging to four species which are used by the community for adaptation after earthquake disaster, namely: D. bulbifera (kentang), D. bulbifera (engal), D. alata (uwi sawa), D. alata (lami), D. alata (uwi kuning ampenan), D. alata (uwi putih ampenan), D. alata (uwi ungu dara kunci), D. alata (uwi putih batu layar), D. alata (uwi ungu batu layar), D. esculenta var. apiculata (surak), D. esculenta var. spinosa (gembili) and D. pentaphylla (buyut). The highest diversity of Dioscorea is found in climate type C3 (8 local types), followed by climate type E (5 local types), climate type D4 (4 local types), climate type B2 (3 local types), and climate type C2 and D3 (1 local type). The local community utilizes the Dioscorea genus in several cultural events including when celebrating the Prophet Muhammad's birthday. The nutritional value of Dioscorea genus is high due to its carbohydrate content (66,09-76,96%), protein content (3.79-10.84%), fat content (1.70-9.58 %) and fiber content (0.32-6.81%). This study shows the potential of Dioscorea to be used as food sources that are cheap, easy to grow, and more adaptive to different environmental conditions to help post-earthquake communities.